The Ballerina and the Minister: Turf Wars and the Australian Government's Exceptional Granting of Political Asylum in 19801. (19th November 2018) - Neumann, Klaus; Taylor, Savitri
Abstract : On 22 April 1980, Australian Foreign Minister Andrew Peacock announced that East German ballet dancer Heidrun Giersch had been granted political asylum. His announcement came as a surprise, because it made Giersch become one of only a handful of people ever to be granted political asylum in Australia. This article explores the circumstances that led to Peacock's decision. We argue that it was not informed by considerations about any persecution faced by Giersch, nor was it the outcome of attempts to shore up support for an Australian boycott of the Moscow Olympic Games, as variously claimed at the time. Rather, it has to be seen in the context of different policies governing the granting of political asylum and the granting of protection following the determination of refugee status, and of conflicts between the Minister for Foreign Affairs and his department, on the one hand, and the Immigration Minister and the Department of Immigration and Ethnic Affairs, on the other, about their respective responsibilities for Australia's refugee and asylum seeker policies.